2005
DOI: 10.1136/qshc.2004.013516
|View full text |Cite
|
Sign up to set email alerts
|

Using real time process measurements to reduce catheter related bloodstream infections in the intensive care unit

Abstract: Problem: Measuring a process of care in real time is essential for continuous quality improvement (CQI). Our inability to measure the process of central venous catheter (CVC) care in real time prevented CQI efforts aimed at reducing catheter related bloodstream infections (CR-BSIs) from these devices. Design: A system was developed for measuring the process of CVC care in real time. We used these new process measurements to continuously monitor the system, guide CQI activities, and deliver performance feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…Miller et al (17) analyzed compliance with an insertion bundle and a maintenance bundle separately and found that only compliance with the maintenance bundle was related to a decreased incidence of CRBSI. Interestingly, the decrease in infection rate in the studies in which the checklist was the primary intervention (18,25) was approximately 45% to 60%, similar to the magnitude of effect observed in the other studies.…”
Section: Discussionsupporting
confidence: 80%
“…Miller et al (17) analyzed compliance with an insertion bundle and a maintenance bundle separately and found that only compliance with the maintenance bundle was related to a decreased incidence of CRBSI. Interestingly, the decrease in infection rate in the studies in which the checklist was the primary intervention (18,25) was approximately 45% to 60%, similar to the magnitude of effect observed in the other studies.…”
Section: Discussionsupporting
confidence: 80%
“…Wall et al studied the impact of process measure interventions in the reduction of catheter related bloodstream infections in the intensive care unit [14]. An interdisciplinary team developed a standardized, nursing checklist for CVC insertion.…”
Section: Discussionmentioning
confidence: 99%
“…These infection control process measures allowed the ICU team to directly monitor adherence to evidencebased guidelines. After two years, the investigators reported a persistent and historically low catheter related bloodstream infection rate, demonstrating that multifaceted programs ensuring maximal adherence with evidence-based infection control guidelines are effective in reducing the incidence of catheter related bloodstream infections in the intensive care setting [14].…”
Section: Discussionmentioning
confidence: 99%
“…With rigorous adherence to infection control techniques, coupled with simulation-based training, such infections can be nearly eliminated. [76][77][78] An analogous transformation must occur in approaches to ICU-acquired delirium and weakness. Although these conditions may occur in the absence of specifi c modifiable risk factors ( Fig 3 ), ICU provider teams must recognize the important role that modifi able risk factors play and use process improvement methods to achieve reductions believed unimaginable today.…”
Section: Coordination: Daily Awakening and Daily Breathingmentioning
confidence: 99%
“…64 Morris et al,65 safety. 76,77 A fi ve-step checklist reduced the central line-associated bloodstream infection rate to near zero across 108 Michigan hospitals. 77 A similar approach applied to ABCDE interventions may yield analogous benefits in preventing ICU-acquired delirium and weakness.…”
Section: Implementing Delirium Monitoringmentioning
confidence: 99%